2020
DOI: 10.1055/s-0040-1719208
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease as a Predictor of Undiagnosed Diabetes or Prediabetes in Dental Patients

Abstract: Objectives The study investigates whether periodontal parameters can identify subjects with undiagnosed diabetes mellitus (DM) or pre-DM in patients seeking dental treatment at a university dental hospital. Materials and Methods Adults older than 35 years, not being diagnosed with DM before and have at least one of the risk factors of DM were included in the study. All subjects received a complete periodontal examination, filled a medical history survey, and a fasting blood glucose measurement was obtained. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…3 Among the factors that increase the risk of severe outcomes and mortality, 4 cardiovascular diseases, cancer, obesity, and diabetes have also been reported to be associated with periodontal diseases. 5 6 7 8 9 10 In this context, the potential relationship between COVID-19 and periodontal diseases has become of major interest and many papers have been published on this issue. The aim of the present scoping review was not only to present the published data regarding potential relationships between periodontal diseases and COVID-19 but also to highlight any gaps in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among the factors that increase the risk of severe outcomes and mortality, 4 cardiovascular diseases, cancer, obesity, and diabetes have also been reported to be associated with periodontal diseases. 5 6 7 8 9 10 In this context, the potential relationship between COVID-19 and periodontal diseases has become of major interest and many papers have been published on this issue. The aim of the present scoping review was not only to present the published data regarding potential relationships between periodontal diseases and COVID-19 but also to highlight any gaps in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Severe periodontal disease may be a warning sign of undiagnosed diabetes [ 9 ]. Periodontal treatment can reduce glycemia among diabetic patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies but one (Lalla et al, 2011) had less than 10 events per variable. In addition, four studies did not include all participants in the analysis (Herman et al, 2015; Hegde et al, 2019; Heji et al, 2020; Su et al, 2020), three dichotomized periodontal predictors using arbitrary thresholds (Herman et al, 2015; Holm et al, 2016; Montero et al, 2021), three used an inappropriate method to select predictors for inclusion in the model (Holm et al, 2016; Grigoriadis et al, 2021; Montero et al, 2021) and one did not account for the complexities in the data, namely sampling fractions in a case–control study (Hegde et al, 2019). Finally, the two studies that reported a PPM (Lalla et al, 2011; Montero et al, 2021) did not assess model performance in terms of both discrimination and calibration, did not account for model overfitting and optimism and did not report the weights assigned to predictors for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were conducted in Western countries, namely three in the United States (Lalla et al, 2011; Herman et al, 2015; Hegde et al, 2019) and one each in Denmark (Holm et al, 2016), Greece (Grigoriadis et al, 2021), the Netherlands (Su et al, 2020) and Spain (Montero et al, 2021). The remaining study was from Saudi Arabia (Heji et al, 2020). While most studies collected primary data, one study used existing data from electronic health records (Hegde et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation